An electrochemically reconstructed WC/WO2–WO3 heterostructure as a highly efficient hydrogen oxidation electrocatalyst. Issue 2 (20th December 2021) - Meng, Ge; Yao, Heliang; Tian, Han; Kong, Fantao; Cui, Xiangzhi; Cao, Shaowen; Chen, Yafeng; Chang, Ziwei; Chen, Chang; Shi, Jianlin
Abstract : A WC/WO2 –WO3 nanosheet heterostructure has been fabricated by an in situ electrochemical reconstruction approach, which significantly elevates the HOR performance by 7 times owing to the synergistic catalytic effect between WC and WO x species. Abstract : Developing a highly efficient and anti-CO poisoning non-noble metal catalyst towards the hydrogen oxidation reaction (HOR) is of great significance for the wide application of proton exchange membrane fuel cells (PEMFCs). Herein, an electrochemical reconstruction approach has been developed to synthesize a WC/WO2 –WO3 nanosheet heterostructure, which exhibits markedly enhanced electrocatalytic activity towards the HOR and excellent CO tolerance. The initially synthesized WC/WO2 octahedral nanoparticles experienced in situ surface oxidation and exfoliation during the electrochemical reconstruction, leading to the in situ formation of WO3 from WO2 and the morphological transition from nanoparticles to a nanosheet structure, which greatly elevates the HOR performance by 7 times and offers a power density of ∼200 mW cm −2 when assembled as an anode catalyst in a single fuel cell. The in situ formed WO3 is proposed to be responsible for the facilitated proton transfer and hydrogen oxidation through the phase transition between WO3 and H x WO3 during the HOR, leading to the accelerated kinetics of H2 adsorption and activation on WC, hydrogen oxidation by H x WO3 phase formation, and final H + desorption from WO2 –WO3, synergistically resulting in greatly enhanced HOR performance together with facilitated electron transfer by metallic WO2 as well as an in situ formed nanosheet structure.